Factors influencing infection by pandemic influenza A(H1N1)pdm09 over three epidemic waves in Singapore. Issue 6 (5th July 2013) - Chen, Mark I. C.; Cook, Alex R.; Lim, Wei Yen; Lin, Raymond; Cui, Lin; Barr, Ian G.; Kelso, Anne; Chow, Vincent T.; Leo, Yee Sin; Hsu, Jung Pu; Shaw, Rob; Chew, Serene; et al.
<x xml:space="preserve">Abstract</x> Introduction Previous influenza pandemics had second and on occasion third waves in many countries that were at times more severe than the initial pandemic waves. Objective This study aims to determine the seroepidemiology of successive waves of H1N1pdm09 infections in Singapore and the overall risks of infection. Methods We performed a cohort study amongst 838 adults, with blood samples provided upon recruitment and at 5 points from 2009 to 2011 and tested by haemagglutination inhibition (HI) with A/California/7/2009 (H1N1pdm09). Surveys on key demographic and clinical information were conducted at regular intervals, and associations between seroconversion and these variables were investigated. Results After the initial wave from June to September 2009, second and third waves occurred from November 2009 to February 2010 and April to June 2010, respectively. Seroconversion was 13·5% during the first wave and decreased to 6·2% and 6·8% in subsequent waves. Across the three waves, the elderly and those with higher starting HI titres were at lower risk of seroconversion, while those with larger households were at greater risk. Those with higher starting HI titres were also less likely to have an acute respiratory infection. Conclusions The second and third waves in Singapore had lower serological attack rates than the first wave. The elderly and those with higher HI titres had lower risk, while those in larger households had higher risk of seroconversion.